From Administrative Compliance to Performance-Based Budgeting: Evaluating Education Fund Effectiveness in Local Government - Ashwad Ashwad; Asna Aneta; Fence M Wantu; Meyko Panigoro (Universitas Teuku Umar, 2026)
This study aims to evaluate the planning and optimize the management of the Education Allocation Fund at the Boalemo Regency Education and Culture Office in supporting improvements in the quality and equity of education services. This study employed a qualitative approach, grounded in a public policy perspective, using descriptive-evaluative methods. Data collection was conducted through in-depth interviews, observations, and documentation studies of education planning and budgeting documents, with key informants from the local government and relevant stakeholders. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, complemented by data validity testing. The results indicate that the planning of the Education Allocation Fund in Boalemo Regency adheres to the regulatory framework and regional planning documents, but remains administrative in nature and is not entirely based on the performance and real needs of educational units. Optimization of education fund management is also suboptimal, particularly in the linkages between budget allocation, program implementation, and achievement of Minimum Service Standards (SPM) indicators. The study's conclusions confirm that increasing the effectiveness of education spending is not solely determined by budget size but is highly dependent on the quality of planning, management, and ongoing monitoring and evaluation mechanisms. Optimizing the Education Allocation Fund requires strengthening data-based planning, performance-based budgeting, and integrated policy evaluation.